Cyber-nationalism phenomena in China and its peculiarities (International relations and international law Journal, 2016)
This article is devoted to analysis of Chinese cyber-nationalism and political effects of new information andcommunication technologies. Expansion of nationalist ideas among Chinese netizens, especially youth challenges both CCP ideological monopoly and traditional view on majority netizens as liberal-democratic and pro-Western group. Also, by analyzing specifics of Chinese cyber-nationalism the article gives some overview on Chinese Internet culture and differences between Chinese and Western approaches towards freedom of speech issues. For CCP cybernationalism is a new challenge, difficult to clear identification due to its skepticism on government’s domestic policy and wide support of PRC’s foreign and military policy especially during its conflicts and arguments with other powers.
Keywords: China; Nationalism; information and communication technology; cyber-nationalism; Communist Party of China